KENYAMANAN TERMAL DI KAWASAN TENGAH KOTA JAKARTA: (Studi Kasus : Apartemen Lavande Residences) - Layosibana Akhirun (Jurnal Teknik Sipil, Arsitek, Perencanaan Wilayah (J-TSIAP), 2024)
This research is to determine the level of thermal comfort based on occupant perception, microclimate and is associated with architectural engineering in human adaptation to urban heat island (UHI). One of the problems in cities is the increase in earth temperature caused by climate change and vertical obstruction. The impact of climate change and vertical obstruction will affect the level of human comfort in their environment. Thermal comfort is an absolute need for the human body, and with its ability, humans also create a built environment to fulfill their comfort both outside and inside a building. This research takes a case study at The Lavande Residence Apartment, which is a residence in the central area of ​​Jakarta. This research uses a descriptive analysis method from data obtained primarily through direct observation and interviews and several other secondary data. The research results show that the suitability of the comfort level based on climate simulations and the comfort calculator is at a neutral level and compared with the perception of residents who still feel comfortable. This perception of thermal comfort after being analyzed is due to architectural engineering efforts carried out by humans in the context of adaptation to climate change.